2020
DOI: 10.18502/jost.v6i2.4783
|View full text |Cite
|
Sign up to set email alerts
|

Total Joint Arthroplasty during Coronavirus Disease-2019 COVID-19 Pandemic

Abstract: Background: Since the outbreak of the novel coronavirus disease-2019 (COVID-19) pandemics many orthopedic elective surgeries have been postponed all over the world. There are several guidelines for resuming elective surgeries during this crisis. In our center (Imam Khomeini hospital, Tehran, Iran), we resumed total joint arthroplasty (TJAs) surgeries using preoperative history taking and physical examination. Here, we report our experience. Methods: From February 2020 to August 2020, we included 165 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Postoperative COVID-19 rates did not differ (3.4% vs. 4.6%, P = 0.34). According to Mortazavi et al's study on 165 arthroplasty patients, only one (0.6%) showed postoperative COVID-19 ( 57 ). The authors suggested the preoperative screening protocol, which includes history taking and physical examination, was effective for screening elective surgical patients in a hospital that provides COVID-19 referral services ( 57 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Postoperative COVID-19 rates did not differ (3.4% vs. 4.6%, P = 0.34). According to Mortazavi et al's study on 165 arthroplasty patients, only one (0.6%) showed postoperative COVID-19 ( 57 ). The authors suggested the preoperative screening protocol, which includes history taking and physical examination, was effective for screening elective surgical patients in a hospital that provides COVID-19 referral services ( 57 ).…”
Section: Discussionmentioning
confidence: 98%
“…According to Mortazavi et al's study on 165 arthroplasty patients, only one (0.6%) showed postoperative COVID-19 ( 57 ). The authors suggested the preoperative screening protocol, which includes history taking and physical examination, was effective for screening elective surgical patients in a hospital that provides COVID-19 referral services ( 57 ). However, their study includes the first peak of COVID-19, which is not as severe as subsequent peaks.…”
Section: Discussionmentioning
confidence: 98%
“…Most previous studies deemed safe resumption of surgeries under safety protocols [ [25] , [26] , [27] , [28] , [29] , [30] , [31] ]. In a study in the UK, Infection with COVID-19 after hip and knee arthroplasty was comparable to the general population (0.5%), and LOS is the only risk factor [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they suggested that their preventive protocol, including history taking and physical examination, was effective for preoperative screening of the patients undergoing arthroplasty in a hospital that was a referral center for COVID-19. Eventually, the study recommended resuming the elective orthopedic surgeries while following the disease prevention protocols (26,27). However, our study reported a higher rate of postoperative COVID-19, which J o u r n a l P r e -p r o o f can be because the study by Mortazavi et al was performed from February to August 2020, when the national incidence of COVID-19 was remarkably lower, presented in Figure 1B.…”
Section: Moreover Another Study By Hernigou Et Al On 104 Patients Undergoing Elective Orthopedic Surgerymentioning
confidence: 99%